Symptoms Other Than Pain in Palliative Care in Portugal. (May 2015) - Gonçalves, Ferraz; Almeida, Ana; Antunes, Catarina; Cardoso, Maria; Carvalho, Margarida; Claro, Maria; Coimbra, Francisca; Diniz, Inês; Fonseca, Bruno; Fradique, Emília; Gonçalves, Edna; Gonçalves, Florbela; et al.
Objective: To study the burden of patients' symptoms other than pain and their treatment by Portuguese palliative care teams. Methods: Of the 21 Portuguese palliative care teams identified, 10 accepted to participate. Data from all patients observed on the 18th week of 2011 were collected. Results: One hundred and sixty-four patients were included in this study. One hundred and fifty-one patients (92%) had cancer. The patients' median age was 71 years (16-95) and 84 (51%) were females. The main symptoms were fatigue (116 [85%]) and depression/sadness (107 [65%]). Many different drugs were used for symptom control and other aims. Symptoms and drugs used here are similar to those practiced in other countries. Conclusion: The practice of palliative care in Portugal seems to be similar to those in other countries.